TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP SHOPEEPAY LATER - syarifah isnaini; ali hardana (Institut agama islam negeri Padangsidimpuan, 2023)
Qardh is a binding legal binding transaction from the creditor after the debtor receives the debt from him. Developments in the field of information technology are now experiencing rapid progress with e-commerce, namely buying and selling transactions or online trading, which is often done in a marker place or an online trading place where sellers only receive money when the goods reach the buyers. Buying and selling through the marketplace and e-commerce is allowed on the condition that the product specifications must be clearly identified and can be handed over as agreed. Shopee is one of the most successful marketplaces and is favored by its users in Indonesia, the qard contract was applied in one of the transaction payment methods, the ShopeePay Later method where this method presents instant loans provided by Shopee users who already have an online shop at Shopee. With the ShopeePay Later method shopee users can enjoy installments with 0% interest. ShopeePay later dispute resolution is resolved through al-shulh and if it is not consensus then it is resolved in the South Jakarta District Court.